2022
DOI: 10.1109/tap.2022.3145430
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Curl-Conforming Vector Bases for Pyramid Cells

Abstract: Advanced applications of the finite element method use hybrid meshes of differently shaped elements that need transition cells between quadrilateral and triangular faced elements. The greatest ease of construction is obtained when, in addition to triangular prisms, one uses also pyramids with a quadrilateral base, as these are the transition elements with the fewest possible faces and edges. A distinctive geometric feature of the pyramid is that its vertex is the point in common with four of its faces, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…As said, a brief historical review of research devoted to the development of basis functions for pyramidal cells can be found in the Introduction of [12]. Here we just reiterate that, in our opinion, the main problem that researchers have had so far in building the bases for the pyramid is to find the simplest and most direct way to build the volume-based vector functions that here, as in [12], we get thanks to simple analytical and geometric considerations.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…As said, a brief historical review of research devoted to the development of basis functions for pyramidal cells can be found in the Introduction of [12]. Here we just reiterate that, in our opinion, the main problem that researchers have had so far in building the bases for the pyramid is to find the simplest and most direct way to build the volume-based vector functions that here, as in [12], we get thanks to simple analytical and geometric considerations.…”
Section: Introductionmentioning
confidence: 83%
“…On the contrary, the few methods so far introduced in [3]- [11] to build the pyramidal bases require specialized knowledge and skills to be understood and have produced higher-order bases different from each other. Although the literature on this topic is not consolidated, as already discussed in the Introduction of [12], the results in [10] nevertheless deserve particular attention.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations